VD_FINDINFO Pron / 2012 / 259 vom 15. November 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, ASSISTANCE JUDICIAIRE, HONORAIRES | 109 CPC (CH), 117 CPC (CH), 122 al. 1 let. a CPC (CH), 122 al. 1 let. b CPC (CH), 122 CPC (CH), 241 CPC (CH)